The peer's point of view: Observing a peer performing an action enhances third-person perspective in adolescents. (April 2017) - Conson, Massimiliano; Salzano, Sara; Frolli, Alessandro; Mazzarella, Elisabetta
Abstract: Adolescents are particularly prone to peer influence. Since group membership modulates the person's tendency to take someone else's viewpoint, here we decided to investigate whether adolescents are influenced by the presence of a peer when taking another person's perspective. A group of adolescents from upper secondary schools in Naples (Italy) had to observe scenes of an actor (an adolescent or an adult) gazing, grasping, gazing/grasping an object or staying still. When required to judge the spatial location of the object, the adolescent participants adopted the actor's viewpoint (third-person perspective) more frequently when the actor was an adolescent rather than when he was an adult and when the adolescent actor grasped the object. Thus, adolescents seem particularly prone to mentally simulate someone else's actions when the other person is a peer. These findings suggest that modulating motor simulation processes via social environmental factors could influence adolescents' perspective taking.